Depression in Adolescence: Implications for School Counsellors - Rice, Kenneth G.; Leffert, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper briefly reviews literature on adolescent depression relevant to school counselling activities and practices. A model of adolescent mental health is presented that serves to underscore the multi-dimensional nature of the development of depression and suggests a variety of strategies to address adolescent depression. We limit discussion to activities involving assessment and referral, counselling, and prevention. Case examples are used to illustrate the application of conceptual issues to actual practice.